Ancient Border Highways: The Minchmoor (Catrail) Road, the Wheel Causeway, the Annandale Forest Road, the Well Path, and the Enterkin - Inglis, Harry R G (Proceedings of the Society of Antiquaries of Scotland, 1924)
The Border hills offer only a limited number of direct passes through which roads can be taken, and while there are perhaps a dozen open passes between north and south, there is only one really accessible highway between the east and the west '” the Tweed valley. This is the context in which the development of these ancient highways must be considered. Each is described in detail.